Implementing a new patient navigator model of care within the emergency department for older adults in Ontario, Canada. - Grace Liu; Amanda Knoepfli; Tracey DasGupta; Naomi Ziegler; Emma Elliot; Mahala English; Sander L Hitzig; Sara J T Guilcher (PLoS ONE)
A Patient Navigator (PN) role was introduced in the Emergency Department (ED) in a large metropolitan hospital in Southern Ontario (Canada) to assist with care transitions. The purpose of this study was to describe the new PN program and type of services provided for older adults in the ED. Given the novelty of the program, it is critical to better understand how a PN ED model of care may help improve the discharge process and ED-community transitions for older adults. This retrospective observational cohort study includes data between November 2020 and October 2021. In this study, the clinical data collected by the PN were analyzed to describe the patient socio-demographics, types of services provided, and outcomes. The PN contacted 95% patients (n = 125) referred to the service in which the median age was 80 (SD = 9.0) consisting of mostly females (74%; n = 92). The PN provided consultations to 79 patients (≤7 days) and 46 patients were admitted to the PN's caseload. For the 46 admitted cases, the PN connected to 52% of the patients on the same day, facilitated 83% of the patients in returning home or supportive setting and provided follow-up care (i.e., phone calls or home visits) for 67 days (median) in the community. This study provides a preliminary depiction of the scope of practice of a PN within an ED setting, and important considerations for decision-makers and/or administrators interested in implementing a PN role in the ED.